Atmospheric corrosion of painted galvanized and 55 % Al-Zn steel sheets: results of 12 years of exposure - Di Sarli, Alejandro Ramón (2012)
Zinc or 55%Al-Zn alloy-coated steel sheets, either bare or covered by different painting systems, have been exposed for 12 years to the action of the urban atmosphere at the CIDEPINT station located in La Plata (34° 50′ South, 57° 53′, West), province of Buenos Aires, Argentina. The samples exposed surface was evaluated through periodical visual inspections, standardized adhesion tests, and electrochemical impedance measurements. The ambient variables monitored were average annual rains and temperatures, time of wetness, sulphur and chloride concentration, relative humidity, and speed and direction of the winds. It was found that in this atmosphere, the corrosion resistance of the bare 55% Al-Zn/steel sheets was higher than of the galvanized steel, and the polyurethane painting system was more protective than the alkyd and epoxy ones, which degraded after 6-7 years of exposure.